THE ROLE OF THE AGRICULTURAL EXTENSION CENTER IN SUPPORTING INSTITUSIONAL DEVELOPMENT IN JENAWI DISTRICT, KARANGANYAR REGENCY - Cahyanto, Ginanjar Dwi; Anantanyu, Sapja; Murdhyanto, Jati; Azizi, Unay Hanifah Khansa; Naat, Agusto Arsianus; Putri, Wydha Sari Hastyana (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
Farmer empowerment and strong institutions through access to information, training, and resources can increase farmer independence and build synergistic collaboration to create collaboration between farmers, government, and other stakeholders. This study aims to analyze agricultural institutions in the fostered area of ​​the Agricultural Extension Center (BPP) of Jenawi District, Karanganyar Regency, Central Java. The methods used were field visits and qualitative data collection through Focus Group Discussion (FGD) with farmers and agricultural extension workers. The analytical technique applied was narrative analysis to understand the views and experiences of informants. The results of the study indicate that farmer institutions and agricultural extension have an important role in increasing farmer productivity and welfare, as well as in supporting technology and information transfer. The BPP institution is under the Infrastructure and Extension Division, the Department of Agriculture, Food and Fisheries of Karanganyar Regency. Agricultural extension institutions run programs referring to the vision, mission, objectives, and performance indicators. Farmer institutions as the main actors require support from the government to help increase farmer capacity both in managing their farmer groups and in their abilities in the agricultural sector.